2016
DOI: 10.1177/0031721716636866
|View full text |Cite
|
Sign up to set email alerts
|

Teacher tenure has a long history and, hopefully, a future

Abstract: Tenure is under fire. Conservatives have long attacked such policies as tenure that constrain the ability of managers to fire whomever they want, but the latest assaults on tenure have invoked liberal egalitarian ideals. With all the problems in education, why are we so fixated on teacher tenure? What is really going on? How did tenure get its start, and why is it still necessary? The author ventures to answer all these questions, positing that tenure is necessary because it significantly strengthens legal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…permanent status, continuous contract/service, and short-term contract/term of office). Tenure discourse underlined the need to increase school principals’ autonomy and ensure continuity and stability in school administration (Jacobs, 2016; Kahlenberg, 2016; Semendinger, 2000). Others considered that non-tenure enhances effectiveness, as it is a tool for accountability and promoting more proactive behaviour (Blaschke, 1974; Nir and Ifanti, 2016; Schleicher, 2012; Semendinger, 2000).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…permanent status, continuous contract/service, and short-term contract/term of office). Tenure discourse underlined the need to increase school principals’ autonomy and ensure continuity and stability in school administration (Jacobs, 2016; Kahlenberg, 2016; Semendinger, 2000). Others considered that non-tenure enhances effectiveness, as it is a tool for accountability and promoting more proactive behaviour (Blaschke, 1974; Nir and Ifanti, 2016; Schleicher, 2012; Semendinger, 2000).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Bauck (1987, p. 92) indicated that '[ … ] tenure was related to effectiveness'; Bess (1998) stated that staff's motivation and productivity is linked more closely to organisational conditions rather than tenure. Permanent position is also seen as a means for reinforcing school principals' authority (European School Heads Association [ESHA] 2008) and protecting from the political interference (Kahlenberg 2016).…”
Section: Introductionmentioning
confidence: 99%
“…While many studies address the controversial nature of teachers’ tenure (Hoffman, 2016; Kahlenberg, 2016; Loeb et al , 2015) and its impact on their behavior and professional considerations (Jones, 2015), the investigation of the effects of tenure on school leaders is relatively limited, mostly focusing on the relation between school leaders’ turnover, teacher retention and student achievements (Béteille et al , 2012). Although some findings suggest that leadership turnover improves organizational performance (Brown, 1982; Denis and Denis, 1995; Virany et al , 1992), more recent studies show that lack of tenure and the frequent replacement of principals may create instability in schools that can potentially undermine efforts for improvement (Gabriel and Dillon, 2011) and may be harmful for organizational performance (Audas et al , 1999; Azoulay et al , 2010).…”
Section: Introductionmentioning
confidence: 99%